Tinjauan Atas Sanksi Dan Imbalan Bunga Perpajakan Dalam Undang-Undang Harmonisasi Peraturan Perpajakan - Khozen, Ismail; Setyowati, Milla Sepliana (Jurnal Hukum & Pembangunan, 2022)
The implementation of interest sanctions and compensation in taxation has undergone changes following the enactment of the Omnibus Law Job Creation in early October 2020. Although the regulation was later deemed unconstitutional, a similar framework has been incorporated into Law No. 7 of 2021 on Tax Harmonization Law (UU HPP). The lack of scholarly research exploring their conceptualization and implementation has motivated us to conduct this study. Our research emphasizes the importance of adhering to principles when designing a regime for imposing sanctions. Comparing two options, utilizing a fixed rate or a floating rate for calculating taxpayer sanctions and interest compensation, the latter option is considered more philosophically equitable. The Indonesian government’s responsibility, after transitioning to the second option, is to ensure the implementation of fairness principles to foster voluntary tax compliance in the long run.